Omega-3 fatty acids intake and risks of dementia and Alzheimer's disease: A meta-analysis. (January 2015) - Wu, Shunquan; Ding, Yingying; Wu, Fuquan; Li, Ruisheng; Hou, Jun; Mao, Panyong
Highlights: Meta-analyses showed that long-chain omega-3 fatty acids intake didn't reduce the risk of dementia or Alzheimer's disease. A higher intake of fish was associated with a 36% lower risk of Alzheimer's disease. An increment of 100 g per week of fish intake was associated with an 11% lower risk of Alzheimer's disease. Abstract: Background: We systematically reviewed the association of omega-3 fatty acids intake with the incidence of dementia and Alzheimer's disease (AD) in this meta-analysis of prospective cohort studies, as evidence from previous studies suggests inconsistent results. Methods: We identified relevant studies by searching PubMed, EmBase, and Web of Science databases up to June 2013. Prospective cohort studies reporting on associations of dietary intake of long-chain omega-3 fatty acids or fish with the incidence of dementia and AD were eligible. Results: Comparing the highest to lowest category of long-chain omega-3 fatty acids intake and fish intake, the pooled relative risks (RRs) for dementia were 0.97 (95% CI 0.85–1.10) and 0.84 (95% CI 0.71–1.01), respectively. Evidence synthesis for AD risk did not show a statistically significant association with long-chain omega-3 fatty acids intake (RR = 0.89, 95% CI 0.74–1.08). However, a higher intake of fish was associated with a 36% (95% CI 8–56%) lower risk of AD. Dose–response meta-analysis showed that an increment of 100 g per week of fish intake was associated with an 11% lower risk of AD (RR = 0.89, 95% CI 0.79–0.99). There was limited evidence of heterogeneity across studies or within subgroups. Conclusion: A higher intake of fish was associated with a lower risk of AD. However, there was no statistical evidence for similar inverse association between long-chain omega-3 fatty acids intake and risk of dementia or AD, nor was there inverse association between fish intake and risk of dementia.